Quantitative Evaluation of Coseismic Deformations Induced by Seismogenic Faulting in Mining Exploration Area During the 2018 Xingwen and 2019 Changning Earthquakes, Sichuan, China - Sun, Chunwei; Ling, Sixiang; Zhao, Siyuan; Wen, Hong; Wang, Sen (Frontiers in Earth Science, 2022)
In the period between December 2018 and July 2019, a series of earthquakes (EQs), including the 16 December 2018 Ms 5.7 Xingwen mainshock and the 17 June 2019 Ms 6.0 Changning mainshock, struck the Changning shale gas exploration field in the southern margin of the Sichuan Basin. The Xingwen and Changning EQs both occurred on concealed faults, which led to hundreds of casualties, and affected a total of over 160 thousand people in southern Sichuan. The aftershock sequences following the Xingwen and Changning EQs were clustered in the vicinity of the Jianwu syncline and Changning anticline, respectively, and occurred mostly at depths of 3–7 km. In this study, coseismic surface deformation measurements obtained through differential interferometric synthetic aperture radar (D-InSAR) data were used to identify the faulting geometries and distributions. The coseismic deformation maps have maximum line-of-sight (LOS) displacements of ∼4.53 cm on the northwest side of the Xingwen EQ source fault and ∼7.84 cm on the southwest side of the Changning EQ source fault. The calculated static Coulomb stress changes indicated that most aftershocks occurred in increasing stress zones following the mainshock ruptures. From the InSAR deformation field, a complicated concealed seismogenic doublet fault was inferred, which predominately exhibited left-lateral strike-slip motion during the Xingwen and Changning EQs. The footwall ramp of the basement fault reactivated first, and resulted in the Xingwen EQ and concentrating stresses beneath the Changning anticline, which induced the Changning EQ half a year later. Compared with previous studies, we proposed that the fault network was lubricated by water that was injected during shale gas exploration, facilitating the occurrence of the Xingwen and Changning EQs. Such work evaluated the coseismic deformations of the Xingwen and Changning EQs, and derived the regional faulting distribution from aftershock sequences. It could provide useful information for monitoring and analyzing seismic activity around the hinge zones of folds in mining exploration areas, which contributes to effective risk assessment of disasters associated with seismic geo-environments.